The History of Vlad Dracula and its Distortion: A Study of Strengthening History Learning Literacy - Jannah, Miftahul; Suwarni, Suwarni (Global Education Journal, 2025)
Talking about civilization, there was a civilization that existed for 1300 years: Islamic civilization. This article aims to find out the history of Dracula and the distortion of Dracula's history. The method used in this study is the historical method. The historical method is used to describe the story of the past based on traces left in the past, with the following steps in writing history: (1) heuristics, (2) criticism, (3) interpretation, and (4) historiography. The study's results indicate that based on the analysis of the discussion, it can be concluded that the history of Dracula comes from Europe, namely Romania. Vlad Dracula was the second son of the ruler of the Wallachian War, Prince Dracul. History also records that Vlad Dracula was one of the most brutal mass murderers. In less than a year of his reign, he had killed thousands of people. The landlords and relatives of Vlad II were killed in a way that had never existed before, namely by impalement. The victims were stabbed from the anus with a stake as big as an adult's arm. Dracula is depicted as a hero in Europe, even though Dracula or Vlad Tepes was a cruel ruler who slaughtered Muslims.